2002
DOI: 10.1016/s0002-9440(10)64871-7
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Reduces Melanosomal Antigen Expression and Recognition of Melanoma Cells by Cytotoxic T Cells

Abstract: In malignant melanoma, tumor-infiltrating lymphocytes are frequently reactive with melanosomal antigens. Achieving complete remissions by peptide therapy is frequently hampered by metastases evading immune recognition. The tumor microenvironment seems to favor reduced expression of target antigens by melanoma cells. Among candidate factors, interferon-gamma (IFN-gamma) (10(2) to 10(3) U/ml) suppressed expression of antigens MART-1, TRP-1, and gp100 by M14 melanoma cells as shown by immunohistology and fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 33 publications
7
38
0
Order By: Relevance
“…More recently, both IFN-␣ and IFN-␥ have been shown to be effective in inducing class I HLA, but with limited effectiveness for Ag induction (39). Furthermore, IFN-␥ sometimes down-regulates Ag expression (40), consistent with our own results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More recently, both IFN-␣ and IFN-␥ have been shown to be effective in inducing class I HLA, but with limited effectiveness for Ag induction (39). Furthermore, IFN-␥ sometimes down-regulates Ag expression (40), consistent with our own results.…”
Section: Discussionsupporting
confidence: 89%
“…Despite its superior stimulation of HLA class I Ag expression (16), IFN-␥ is a poor inducer of melanocytic Ags (Ref. 39 and this work), and may even repress Ag expression in some tumors (40). Our own experience has shown that stimulation of A375 cells with IFN-␥ fails to elicit the enhanced cytotoxicity induced by IFN-␤.…”
Section: Discussionmentioning
confidence: 78%
“…Of the pigmentation genes, DCT showed a drastic decrease of around 80%. Similar observations were also reported during the course of another study (17,18). TYRP1 and TYR were decreased to a lesser extent across different primary cultures treated with IFN-γ ( Fig.…”
Section: Ifn-γ Causes Cellular Hypopigmentation By Arresting Melanosomesupporting
confidence: 89%
“…21,22,34,35 According to our results, this reduction most likely originates from the downregulation of transcription factor MITF-M by these cytokines. We provide the first evidence that IL-1a and IL-1b are additional cytokines that reduce the expression of MITF-M.…”
Section: Discussionsupporting
confidence: 59%
“…In a previous study, IFN-c was shown to reduce by up to 78% the cytotoxicity of anti-Melan-A/MART-1 26-35 CTL, despite the stimulatory effect of IFN-c on MHC class I expression and antigen presentation. 22 This reduction is most likely due to the induction of the immunoproteasome, which does not process the Melan-A/MART-1 [26][27][28][29][30][31][32][33][34][35] peptide. 42 Data of a recent study suggest that IL-1b is not able to induce the immunoproteasome.…”
Section: Tumor Immunologymentioning
confidence: 99%